Coccolithophore assemblage changes over the past 9 kyrs BP from a climate hotspot in Tasmania, southeast Australia - Bradley Paine; Linda Armbrecht; Christopher Bolch; Gustaaf Hallegraeff (2023)
Predicting phytoplankton responses to a changing climate on Tasmania's east coast is presently based on short-term plankton data sets (∼75 years). However, to better predict future phytoplankton composition, it is crucial to understand longer-term variations from geological records. A particularly important group are the coccolithophores given their vital contribution to the oceanic carbon pump. Here, we expand the archive of coccolithophores in southeast Australian waters by analysing coccolith assemblages in a 268 cm-long marine sediment core collected off Maria Island, Tasmania, using light and scanning electron microscopy in combination with sedimentary ancient DNA ( sed aDNA) techniques. Coccoliths underwent a shift from a cold to warm-water adapted assemblage at ∼8.2 kyrs BP expressed by a transition in species dominance from the cold-water species Gephyrocapsa muellerae to the warmer-water species Emiliania huxleyi Type A. A period of coccolithophore community instability characterised by reduced diversity and species richness was also detected spanning ∼900 yrs. between 6 and 5 kyrs BP. The latter may be associated with a Mid-Holocene warm period in the Southern Ocean as well as sea-level rise changing the study site from a shallow coastal to deep water habitat. Emiliania huxleyi coccoliths displayed the highest total relative abundance, but less prevalent larger taxa ( Calcidiscus , Coccolithus , Helicosphaera ) accounted for >50% of total estimated coccolith CaCO 3 sequestration, indicating that relatively scarce, densely calcified species do the ‘heavy-lifting’ of this process. Analysis of sed aDNA revealed coccolithophores contributed ∼44% to the total palaeo eukaryote composition, underlining their importance as part of the marine ecosystem in the study region. The detection of oceanographic shifts and subsequent coccolithophore assemblage composition, including past transitions of species dominance, offer valuable insight into the biological future of southeast Australian waters.